2023
DOI: 10.1021/acsomega.2c08013
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous and Orbital Adipose Tissues: Intrinsic Differences in Carotenoid Contents and Lipidomic Compositions

Abstract: The color difference in human subcutaneous fat (SF) and orbital fat (OF) is apparent, but the reasons have been rarely elaborated. We speculate that differences in carotenoid and lipid contents may account for the discrepancy in color. In this study, the intrinsic differences in SF and OF were analyzed using ultrahigh-performance liquid chromatography coupled with Q-Exactive liquid chromatography mass spectrometry/mass spectrometry (UPLC-QE Plus LC−MS/MS). Lipid profiling was performed in an independent batch.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The difference between orbital fat and subcutaneous fat is not only reflected in the histological structure, but also different in carotenoids and other components. Kaili Zhang et al [ 19 ] found that the carotenoid content of orbital septum fat is significantly lower than that of subcutaneous fat, while the carotenoid content of central fat pad is significantly higher than that of medial fat pad, [ 20 ] which is also the main reason for the color difference of orbital fat in different regions. Ahmadi et al [ 21 ] found a tendency to decrease carotenoid content in the central fat pad of patients with degenerative ptosis compared to the normal population through case–control studies.…”
Section: Histological Characteristics Of Orbital Fatmentioning
confidence: 99%
“…The difference between orbital fat and subcutaneous fat is not only reflected in the histological structure, but also different in carotenoids and other components. Kaili Zhang et al [ 19 ] found that the carotenoid content of orbital septum fat is significantly lower than that of subcutaneous fat, while the carotenoid content of central fat pad is significantly higher than that of medial fat pad, [ 20 ] which is also the main reason for the color difference of orbital fat in different regions. Ahmadi et al [ 21 ] found a tendency to decrease carotenoid content in the central fat pad of patients with degenerative ptosis compared to the normal population through case–control studies.…”
Section: Histological Characteristics Of Orbital Fatmentioning
confidence: 99%